In vitro and in vivo evaluation of carbonate apatite-collagen scaffolds with some cytokines for bone tissue engineering - Sherman Salim; Maretaningtias Dwi Ariani (Wolters Kluwer Medknow Publications, 2015)
Background: Collagen is regarded as one of the most useful biomaterials. We tried to combine collagen and carbonate apatite (CA) with some cytokines in order to enhance bone formation ability. In this study, we found that CA-collagen sponge (CA-CS) was a possible candidate of newly graft material for bone formation. Materials and Methods: CA-CS was fabricated by the following procedure. One wt% of pig hide collagen solution (Nippon Meat Packers. Inc., Tokyo, Japan) was neutralized with 0.1 N NaOH, and then mixed immediately 243 mg apatite powder with 0.06 M carbonate contents. After centrifugation at 1500 rpm for 10 min, excess water was removed, and the mixture was packed into Teflon molds (5.0 mm × 2.0 mm). Each 10 µg of basic fibroblast growth factor (bFGF) and recombinant human bone morphogenetic protein-2 (rh-BMP2) were involved in these sponges. Then these scaffolds frozen at −80°C for 2 h and dried in a freeze dry machine for 24 h. CA-CS without cytokines were also prepared as a control. Mouse osteoblast-like cell (MC3T3-E1) proliferations in these scaffolds were investigated by 3-day in vitro cell culture using MTT assay examination. Ten New Zealand rabbits (weight: 3-3.5 kg) were used in this in vivo study. After 3 weeks of placement, the scaffolds, rabbits were sacrificed, and bone formation in the sockets was evaluated histologically and histomorphometrically. Results and Conclusion: By histological observation and measurement of bone area ratio, CA-CS with cytokines showed higher bone formation ability (bFGF/CA-CS: 50.7 ± 7.3%, rh-BMP2/CA-CS: 54.2 ± 5.0%) than other groups. From the limited results of this study, it is suggested that CA collagen scaffolds with some cytokines may become an attractive scaffold for bone regeneration.